Role of adjuvant chemotherapy in T2N0M0 periampullary cancers. Issue 5 (28th December 2016) - Ostwal, Vikas; Harris, Caleb; Sirohi, Bhawna; Goel, Mahesh; Bal, Munita; Kannan, Sadhana; Shrikhande, Shailesh V
Abstract: Aims: Surgery is the only modality that offers cure for periampullary adenocarcinoma. However, surgery alone results in failure in 60% of patients. Studies have shown some benefits of chemotherapy in node positive and higher tumor stage patients. We sought to determine the role of adjuvant chemotherapy in early tumors with uninvolved nodes. Methods: A retrospective analysis of a prospectively maintained database of patients resected of periampullary tumors from 2007 to 2014 was performed. Patients were studied for adverse risk factors, adjuvant therapy received and the survival. Results: Of 105 patients, 14 patients received adjuvant chemotherapy and 85 were observed. After a median follow‐up of over 36 months, the overall 3‐year survival was 94.2% in the observed group and 100% in the group that received chemotherapy (P = 0.33), with the 3‐year disease‐free survival being 81.9% and 90.9%, respectively, (P = 0.477). Serum CA 19‐9 levels above 100 U/mL were a poor prognostic factor. Conclusion: This study did not find a benefit with the use of adjuvant chemotherapy, but chemotherapy might improve survival. The benefit for adjuvant chemotherapy needs further confirmation in prospective trials.